Quadriceps neuromuscular function in women with patellofemoral pain: Influences of the type of the task and the level of pain - Briani, Ronaldo Valdir [UNESP]; Silva, Danilo De Oliveira [UNESP]; Floride, Carolina Silva; Aragao, Fernando Amancio; Albuquerque, Carlos Eduardo de; Magalhaes, Fernando Henrique; Azevedo, Fabio Micolis de [UNESP] (Public Library Science, 2018)
The present study aimed at investigating whether the neuromuscular system behaves differently (in terms of force and muscle activity generation) as a function of the task being performed (i.e. maximal voluntary efforts vs stair negotiation) and the presence of patellofemoral pain (PFP) and possible influences of pain intensity. Thirty-eight women with (n = 19) and without PFP (n = 19) had their knee strength (extension joint torque) measured during maximal voluntary isometric contractions (MVIC) and electromyography (EMG) data recorded during both MVIC and stair ascent tasks, which were performed before and after a loading protocol designed to exacerbate pain symptoms. Women with PFP displayed lower levels of vastus medialis (p = 0.002) and vastus lateralis (p = 0.032) EMG activation during MVIC assessments. Conversely, the PFP group showed higher levels of vastus medialis muscle activity during stair climbing (p = 0.007), which happened exclusively after the loading protocol. Similarly, women with PFP displayed lower knee extensor torque only during the MVIC tests performed after the loading protocol, which was moderately correlated with the increase in self-reported pain (p = 0.041, r = 0.37), whereas the changes in EMG activity during stair ascent were not correlated with changes in pain intensity (p = 0.215, r = 0.12). These results suggest that, in comparison to pain-free controls, women with PFP display lower levels of quadriceps EMG activation during maximal contractions, but higher activation during dynamic tasks (stair ascent). In addition, the moderate association between the decrease in knee extensor torque and increase in self-reported pain indicates that care should be taken by clinicians during quadriceps strength evaluation in women with PFP, as misleading outcomes may emerge if the intensity of knee pain is not considered during screening. Additionally, rehabilitation strategies should focus on both restoring neuromuscular control and increasing muscle strength.